Toughening polyamide 6 nanocomposites with maleic anhydride grafted polyethylene octene - Wahit, Mat Uzir; Hassan, Azman; Koay, Yee Farn; Othman, Norhayani; Mokhtar, Munirah (2006)
Rubber toughened nanocomposites consisting of ternary blends of polyamide 6 (PA 6), maleic anhydride grafted polyethylene octene (POEgMAH) and organoclay montmorillonite (MMT) were prepared by melt compounding followed by injection moulding. The organoclay content was kept constant at 4 wt% while the POEgMAH content was varied between 5 to 20 wt%. The mechanical properties were studied through tensile, flexural and impact properties. The scanning electron microscope (SEM) and X-ray diffraction (XRD) were used to examine the morphology of the nanocomposties. The results showed that, the incorporation of 4 wt% organoclay significantly increased the stiffness and strength but at the expense of the toughness. Izod impact measurement indicated that the addition of POEgMAH led to a significant improvement in the impact strength of the nanocomposites. X-ray diffraction analysis (XRD) revealed that an intercalation organoclay silicate layer structure was formed in rubber-toughened PA6 nanocomposites. SEM study revealed a two-phase morphology where POE, as droplets was dispersed finely and uniformly in the PA6 matrix.